Предмет: Алгебра,
автор: speed3v
Представьте в виде произведения выражения: (3а-1)^2-(а+2)^2
Ответы
Автор ответа:
0
(3a-1)^2-(a+2)^2=(9a^2-6a+1)-(a^2+4a+4)=9a^2-a^2-6a-4a-4-1=8a^2-10a-3
8a^2-10a-3=0
a=10⁺₋/2*8=10⁺₋2/16
a₁=10-2/16=8/16=0,5
a₂=10+3/16=13/16=0,8125
8a^2-10a-3=0
a=10⁺₋/2*8=10⁺₋2/16
a₁=10-2/16=8/16=0,5
a₂=10+3/16=13/16=0,8125
Похожие вопросы
Предмет: Математика,
автор: KrutoyAibek
Предмет: Биология,
автор: ayimarysbekkyzy
Предмет: Химия,
автор: asaskpo
Предмет: Математика,
автор: pop42442
Предмет: География,
автор: Аноним